#### Answer

$y=2(x-3)^2-2$

#### Work Step by Step

We begin with:
$f(x)=x^2$
We are told to stretch vertically by a factor of 2, shift down 2 units, and shift 3 units right. This means: $y=2f(x-3)-2$. Thus we get:
$y=2(x-3)^2-2$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$y=2(x-3)^2-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.